1998
DOI: 10.1046/j.1525-1594.1998.06041.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Intravenously Administered Recombinant Human Erythropoietin on the Immune Response of Uremic Patients Maintained on Regular Hemodialysis

Abstract: The uremic patient on regular hemodialysis (RHD) is subjected to a wide range of immune modulators including the uremic state per se, multiple transfusions and exposure to bioincompatible materials and endotoxins. Erythropoietin (EPO) therapy may raise concern about its potential influence on this complex scenario. To envisage this issue, 15 adequately selected patients, stable on RHD, were randomly assigned in a 2:1 ratio into EPO and placebo groups. After initial assessment and determination of baseline valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…When added to a perfusion fluid, NP causes a decrease in erythropoietin mRNA levels. However, erythropoietin administration to patients on dialysis inhibits the release of NP only in the initial phase (23). In vivo high NP concentrations in renal tissue probably aggravate anaemia, which accompanies inflammation (41).…”
Section: Neopterin and Haematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…When added to a perfusion fluid, NP causes a decrease in erythropoietin mRNA levels. However, erythropoietin administration to patients on dialysis inhibits the release of NP only in the initial phase (23). In vivo high NP concentrations in renal tissue probably aggravate anaemia, which accompanies inflammation (41).…”
Section: Neopterin and Haematopoiesismentioning
confidence: 99%
“…NP is stable for a few weeks when kept below –20 °C (8). It is measured by enzyme‐linked immunosorbent assay (ELISA), radioimmunoassay (RIA) (23) and high‐performance liquid chromatography (HPLC) (11, 24). Serum NP concentration of 10 nmol/L is accepted as the upper normal limit (6).…”
Section: Introductionmentioning
confidence: 99%
“…After few months of rhEPO therapy decreased production of pro-inflammatory cytokines (IL-6 and TNF-α) and elevated secretion of anti-inflammatory IL-10 in whole blood cell cultures stimulated with PHA were also observed [30,31] . There were also studies showing higher concentration of TNF-α in serum of HD patients receiving rhEPO [32] but its level was determined after the dialysis procedure, during which the release of large amount of pro-inflammatory cytokines occurs [25] . Bryl et al [29,31] and Trzonkowski et al [30] demonstrated that rhEPO acts directly on production of cytokines by whole blood cells in vitro.…”
Section: Role Of Erythropoietin and Its Recep-tor In Modulating Immunmentioning
confidence: 99%